PROTOTYPE MODELING OF A WEB-BASED INFORMATION SYSTEM FOR INCOMING AND OUTCOMING MAIL (CASE STUDY: AZ ZUHRA INSTITUTE) - Suwarti, Suwarti; Zulkifli, Zulkifli (I N F O R M A T I K A, 2023)
Every company or government and private agency has a different document management process which is managed by the administration department. Mail management is very necessary in an organization as a source of data or information that is useful for the progress of the organization. At the Az Zuhra Institute, the process of managing incoming and outgoing mail is not running optimally because it is still done optimally by recording in a ledger because it is still done by recording in a ledger, namely in an agenda book. With the manual method, problems often occur that make data difficult to manage properly. With the large number of letters created and received, when at any time they need information about old incoming or outgoing letters, officers must first open the old data and look for them one by one, so it is not efficient. Lack of space for archival storage means that data is easily lost and the reports produced are not accurate. Designing a prototype web-based incoming and outgoing mail information system using the waterfall method is a solution for solving current problems. The aim of this research is that it is hoped that the existence of a computerized system will make the process of managing letters easier and can also influence employee performance so that they can carry out their duties well for the smooth running of their work activities.